Research on Full-Section Anchor Cable and C-Shaped Tube Support System of Deep Layer Roadway. (16th February 2021) - Shan, Renliang; Zhang, Shupeng; Huang, Pengcheng; Liu, Weijun
Abstract : Deep roadway deformation due to soft rock, rock dip, and horizontal tectonic stress is uneven and asymmetrical primarily in large loose zones. Traditional anchor support is influenced by the yield strength and shear strength of the anchors and has a limited prestress capacity or shear resistance. When the roadway roof is laminated rock or when the roadway passes through layered rock or rock interfaces, interlayer sliding commonly occurs, which can easily lead to anchor cables being sheared off. The tape tunnel in the Zhengling Mine passes through several rock strata and requires anchors to achieve a high shear resistance and prestress. To solve these problems, an anchor cable and C-shaped tube that can bear lateral shear forces were developed, and a full-section anchor cable and C-shaped tube support system were created based on extruded arch theory. Numerical results from FLAC 3D show that the new scheme effectively controls surface convergence and plastic zone extension. Field tests have demonstrated that the amount of surface displacement was at least 42% smaller in the new support scheme. The extruded arch formed by the highly prestressed anchor cable and concrete spray layer can effectively control the bulking load within the loose zone, and the ACC effectively resists interlayer shear.